Effect of chemical surface treatment on thermal stability of poly(ethylene terephthalate) films used in flexible circuits - Severgnini V.L.S. (2005)
Acid etching is a useful method of surface treatment for poly(ethylene terephthalate) (PET) films to allow adherence of Ni-P alloys deposited by the electroless technique for the fabrication of flexible circuits. The lifetime of such devices depends mainly on reasonable durability and unique mechanical and electrical properties. This study focused on the analysis of the influence of the surface treatment on the stability of the polymer film in order to determine the lifetime of these devices. Etched PET films were analyzed by thermogravimetry and Fourier-transform infrared spectroscopy. The results indicate that acid etching does not alter the PET thermograms. FTIR spectra of the residues indicate a degradation mechanism based on the breaking of the main chain to form carboxylic acid and ethylene glycol. The surface treatment mainly oxidized the outer layers of the polymer and as a consequence did not show significant decrease in the stability of the polymer film. © 2004 Elsevier Ltd. All rights reserved.